Factors preventing non-English major college students from achieving the required English proficiency level standard: A case at a college in Can Tho city : - Pham, Thanh Huyền (Trường đại học Cần Thơ, 2018)
This research is conducted to investigate the extent to which non-English major college students think they can achieve English proficiency level standard (level B1). Find out the factors preventing non-English major college students from achieving that required proficiency level standard.